Insights into lysosome-related organelle biogenesis: melanosome as a model organelle - Barral, Duarte C.; Delevoye, Cédric; Larue, Lionel; Seabra, Miguel C.; Raposo, Graça; Setty, Subba Rao Gangi (Frontiers in Cell and Developmental Biology, 2026)
Lysosome-related organelles (LROs) encompass specialized intracellular compartments that share features with lysosomes while fulfilling distinct physiological roles, with melanosomes representing the best-studied example. Melanosome biogenesis relies on coordinated trafficking, sorting, and membrane remodeling mechanisms that diverge from the canonical endolysosomal pathways. These organelles ultimately serve as the primary sites of melanin synthesis and deposition. In the skin, melanin is produced by melanocytes and transferred to keratinocytes, where it achieves its essential photoprotective role. Melanin is a remarkably diverse and ancient polymer, with eumelanin, pheomelanin, and neuromelanin constituting the major mammalian forms. Understanding melanin biology also requires tracing the origins of melanocytes, which were once thought to derive exclusively from the neural crest but are now known to arise from multiple embryonic lineages. This expanded view of melanocyte ontogeny has revealed unexpected pigment cell populations in several internal organs. Beyond these developmental aspects, melanin performs multifaceted physiological functions that extend far beyond photoprotection of the skin. Here, we discuss the current knowledge on the origin of melanosomes from endosomal precursors, the transfer of melanin from melanocytes to keratinocytes, and its fate in these recipient cells within the epidermis. Additionally, the intriguing mysteries surrounding melanosomes in the retinal pigment epithelium are addressed, as well as the broader diversity, origins, and physiological roles of melanin in other cell types. Taken together, these perspectives highlight the melanosome as both a model LRO and an organellar hub for deciphering melanin diversity, cellular origins, and the wide-ranging physiological roles of this pigment in vertebrate biology.